EVALUASI PENGGUNAAN OBAT ANTIPLATELET TERHADAP KEJADIAN PERDARAHAN SALURAN CERNA BESERTA FAKTOR RESIKONYA PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT BETHESDA YOGYAKARTA - , MARTHA EVY SUSANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction: Antiplatelet is widely used drug in patients with ischemic stroke. In patients with ischemic stroke in which the high recurrence, the use of antiplatelet recommended to reduce or prevent the incidence of recurrent stroke and other cardiovascular events. Although antiplatelet therapy is effective in reducing the incidence of stroke, but gastrointestinal bleeding is the side effect of antiplatelet, may even increase mortality, with risk factors that increase the incidence of gastrointestinal bleeding. Methods: This study includes an observational study with cross-sectional method of frequency study using stroke registers data from January 2011 to December 2013, and the case-control method that use secondary data to search the medical records of patients from January 2010 to December 2013. For cases selected group of patients newly diagnosed with ischemic stroke who received antiplatelet therapy and gastrointestinal bleeding (60 patients), compared with a control group that not experienced gastrointestinal bleeding (60 patients). Then retrospectively studied the risk factors that may increase the incidence of gastrointestinal bleeding. Outcome of the study is gastrointestinal bleeding. Results:In frequency studies, the number of ischemic stroke patients for 3 years (January 2011 to December 2013) is 1,267 patients, and gastrointestinal bleeding in 52 patients. Based on bivariate analysis, the risk factors that affect the gastrointestinal bleeding was the use of antiplatelet with anticoagulant (p=0.003